PENGARUH PENGGUNAAN METODE JARIMATIKA TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS V SDN PRAPAG LOR 01 - Jermis Bagus Bakhtiyar; Farhan Saefudin Wahid; Ubaedillah (SOKO GURU: Jurnal Ilmu Pendidikan, 2022)
The purpose of this study was to determine the effect of using the Jarimatika method on the motivation and learning outcomes of fifth graders at SDN Prapag Lor 01. To answer these problems, the researchers used two data analyzes, namely, to test the effect of the Jarimatika method on learning motivation with the Wilcoxon match pairs test and to test the effect of the Jarimatika method on learning outcomes using the Paired Sample t-test. The research subjects were 21 respondents. Collecting data using a questionnaire instrument to collect data on students' learning motivation and mathematics learning outcomes obtained through tests and student scores documents. For other information, researchers used interviews. Based on the results of the study, it was found that: 1) The average result of learning motivation before using the Jarimatika method was 39.14 in the poor category. 2) The average result of learning motivation after using the Jarimatika method is 67.33 in the very good category. 3) The researcher then analyzed the data using the Wilcoxon match pairs test, the value (tcount = 0 < ttable = 2,080) at a significance level of 5%. Thus, it can be concluded that there is an influence of the Jarimatika method on the motivation to learn mathematics in third grade students of SDN Prapag Lor 01 in the academic year 2021/2022. 4). The average result of learning mathematics before using the Jarimatika method was 43.33 in the poor category. 5) The average result of learning mathematics after using the Jarimatika method is 80.48 in the very good category. 6) Next, the researcher analyzed the data by using the Paired Sample t-test. The value (tcount = 11.2 > ttable = 2.086) at a significance level of 5%. Thus, it can be concluded that there is an influence of the Jarimatika method on the learning outcomes of multiplication operations mathematics in third grade students of SDN Prapag Lor 01 in the 2021/2022 academic year.